Refinement of the normal Eötvös matrix and its influence on the estimation of the deflections of the vertical - MANOUSSAKIS, Gerassimos; KORAKITIS, Romylos (Contributions to Geophysics and Geodesy, 2015)
The elements of the Eötvös matrix, usually determined by torsion balance measurements, are useful in many geodetic applications. We present a method for the computation of the elements of the normal Eötvös matrix at a point on the Earth’s physical surface, resulting in an improvement in the determination of the deflection of the vertical at intermediate points of a network. In the process, we also present analytical expressions for the computation of the components of the deflection of the vertical. From those expressions and using also a numerical example, we show that the proposed refinement is not completely negligible.